PENGARUH PEMBELAJARAN DARING TERHADAP MOTIVASI DAN HASIL BELAJAR KOGNITIF PESERTA DIDIK DI SMA NEGERI 3 TANJUNG JABUNG TIMUR - Patmi, Patmi; Hamidah, Afreni; Anggereini, Evita (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2021)
This study aims as a teaching and learning activity that utilizes a network or internet connection so that communication is established between teachers and students without direct contact. Problems faced in online learning include: weak signal, the application used is sometimes problematic, and many more problems that will be caused in online learning. The results of the observations made by the researchers did the learning motivation of students in biology subjects was still very low, there were some students who were sometimes not enthusiastic in learning so that the learning outcomes obtained were still limited to the KKM value, this can be seen from the average test scores during learning Biology during the COVID-19 pandemic. The purpose of this study was to determine the effect of online learning on students' learning motivation and to determine the effect of online learning on students' cognitive learning outcomes. This type of quantitative research with a descriptive approach. The research subjects were students of class XI Science Department at SMA Negeri 3 Tanjung Jabung Timur. The results of this study are (1) on the motion system material in humans, students' learning motivation with online learning falls into the good category on the indicators of material delivery by using links and using different methods and applications; (2) cognitive learning outcomes in online learning during the pandemic are not much different when compared to face-to-face learning. Although in practice there are deficiencies found, but there is no other choice but to optimize online learning, because in current conditions only technology can be a bridge in transferring knowledge from teachers to students.